Validating academic integrity survey (AIS): an application of exploratory and confirmatory factor analytic procedures - Nordin, Mohamad Sahari (Springer International Publishing, 2016)
Abstract This study concerned validating academic integrity survey (AIS), a measure developed in 2010 to investigate academic integrity practices in a Malaysian university. It also examined the usefulness of the measure across gender and nationality of the participants (undergraduates of Nigerian and Malaysian public universities). The sample size comprised 450 students selected via quota sampling technique. The findings supported the multidimensionality of academic dishonesty. Also, strong evidence of convergent and discriminant validity, and construct reliability were generated for the revised AIS. The testing of moderating effects yielded two outcomes. While the gender invariant analysis produced evidence that the three-dimensional model was not moderated by gender; the nationality effect was inconclusive, probably due to a noticeable imbalance in respondent distribution for the nationality group. The significance of this study lies not only in the rigorous statistical methods deployed to validate the dimension and psychometric properties of the AIS; but establishing the gender invariance of the model. It is understood from the findings that although male and female students may vary in their academic misconducts, the underlying factors for these conducts are the same and can be addressed effectively using a non-discriminating approach.